2001
DOI: 10.1007/s004150170135
|View full text |Cite
|
Sign up to set email alerts
|

Neurological complications of primary Sjögren's syndrome

Abstract: Neurological complications of PSS are frequent since they were present in 40% (10/25) of patients in a consecutive series of patients from a department of Internal Medicine. Although PNS involvement predominates, complications of PSS affecting the brain or spinal cord are not rare, with subcortical dysfunction as the main finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
1
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(124 citation statements)
references
References 33 publications
(44 reference statements)
7
106
1
10
Order By: Relevance
“…The results from other countries suggest that patients with PSS display cognitive impairments in attention, memory, speed of information processing, and executive function, indicating a pattern of frontal-subcortical dysfunction 9 . Psychiatric alterations have also been reported to be associated with cognitive impairments related to diffuse encephalic manifestations 5,10 .…”
mentioning
confidence: 90%
“…The results from other countries suggest that patients with PSS display cognitive impairments in attention, memory, speed of information processing, and executive function, indicating a pattern of frontal-subcortical dysfunction 9 . Psychiatric alterations have also been reported to be associated with cognitive impairments related to diffuse encephalic manifestations 5,10 .…”
mentioning
confidence: 90%
“…63 Case reports have described a patient with an amnestic syndrome 64 and another with Klüver-Bucy-like symptoms 65 in CNS Whipple’s disease, which highlights the variable presentation in this disease. Sjögren’s syndrome 6669 and Behçet’s disease 70 –72 — both autoimmune disorders— can involve the CNS as well, causing cognitive and personality changes (Table 2). …”
Section: Encephalopathy In Lupus and Other Systemic Syndromesmentioning
confidence: 99%
“…It was concluded that the local decrease of neuropeptides in the salivary glands may contribute to the atrophy and functional deficiency of salivary glands (Lafitte, 2002;Batbayar et al, 2004). Our preliminary results showed that the PEF treatment exerted similar effect on the peptidergic innervation pattern of sweat glands, the minor salivary glands of tongue and oral mucosa of the rat (unpublished data).…”
Section: Modification Of Innervation In Salivary Glandmentioning
confidence: 54%